The Outcome of Patients with Sepsis at Tarakan Hospital Central Jakarta in 2018 - Dharmawan, Ade; Istia, Mieke Joseba; Tan, Henny Tannady; Suparto, Suparto; Anastasia, Monica Cherlady; Layanto, Nicolas (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2021)
Background: Sepsis is a common, life-threatening organ dysfunction caused by a dysregulated host response to infection. In 2017, estimated cases for sepsis reached 48.9 million worldwide, with 11 million deaths. Adequate antibiotic therapy is crucial for the treatment of sepsis. Purposes: The objective of this study is to find factors related to sepsis patient outcomes. Methods: We conducted a 1-year retrospective descriptive study with the inclusion criteria of all adult sepsis patients in Tarakan District Hospital in 2018. We compiled 39 samples that fit the inclusion criteria. Results: The distribution gender of this study were 51.2% female and 48.8% male patients; with most patients in the age of 65 years old (53.8%), 7 days in the length of stay (72%), and the most common source of infection was gastrointestinal (33.3%) followed by lungs (28.2%). Conclusion: We found a mortality rate of 59%, with the most common source of infection leading to death was the lungs (81.2%) and treated with single ceftriaxone antibiotic therapy (78.3%). Another factor associated with mortality is inadequate single antibiotic therapy.